Adequação de demandas funcionais de atividades para a participação escolar de crianças com disfu'nções neuromotoras - Pereira, Débora Morais [UNESP]; Araújo, Rita de Cássia Tibério [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (My University, 2010)
The school participation is a prerequisite for the construction of knowledge, learning and development. Neurological deficits may affect child's ability to explore the environment and engage in typical activities. Considering the importance of encouraging professionals in the field of education to conduct simple adjustments in school activities of daily life, this study aimed to adapt, with low cost materials, resources of entertainment and educational for children with neuromotor disorders . It was objects of this study eight resources prescribed and designed for three children diagnosed with cerebral palsy: domino, puzzle, memory game, moving magnetized alphabet, crossword, doll body scheme, adaptation of pencils for writing and bracelet sinker.The analysis of these resources occurred in the parameters of conventional design and management skills, followed by identifying the limiting conditions of the motor skills of the cases observed, indicating the materials used in the adaptation and possible uses. This study provides subsidy for implementation of teaching strategies in the care of students with neuromotor disorders.

A participação escolar é condição essencial para a construção do conhecimento, aprendizagem e desenvolvimento. Déficits neurológicos podem afetar a capacidade da criança para explorar o ambiente e se engajar em atividades típicas. Considerando a importância de se incentivar profissionais da área da educação a realizarem adaptações simples nas atividades escolares do dia-a-dia, este trabalho teve como objetivo adaptar, com materiais de baixo custo, recursos lúdicos e didáticos para crianças com distúrbios neuromotores. Foram objetos de estudo oito recursos adaptados prescritos e elaborados para três crian- ças com diagnóstico de paralisia cerebral: dominó, quebra-cabeça, jogo de memória, alfabeto móvel imantado, cruzadinha, boneco de esquema corporal, adaptação de lápis para escrita e pulseira de chumbada. A análise desses recursos ocorreu sob parâmetros do design convencional e das competências de manuseio, seguida pela identificação das condições limitantes da capacidade motora dos casos observados, indicação dos materiais utilizados na adaptação e possíveis finalidades. Este estudo oferece subsídios para a implementação de estratégias pedagógicas no atendimento do aluno com distúrbios neuromotores.
Fitness of functional demands of activities for the school particitation of children with neuromotor dysfunction
Keywords: educação especial; deficiencia física; recurso adaptado